AB0945 Secukinumab efficacy in patients with active psoriatic arthritis: pooled analysis of four phase 3 trials by prior anti-tnf therapy and concomitant methotrexate use. (12th June 2018) - Kirkham, B.; Mease, P.J.; Nash, P.; Balsa, A.; Combe, B.; Rech, J.; Martin, R.; Ligozio, G.; Abrams, K.; Pricop, L.; ,
Abstract : Background: Secukinumab has demonstrated rapid, significant and sustained improvement in the signs and symptoms of psoriatic arthritis (PsA) in multiple Phase 3 studies. 1–3 Objectives: To report pooled efficacy results for secukinumab versus placebo at Week (Wk) 16 in PsA patients (pts) by previous anti-TNF therapy and with or without concomitant methotrexate (MTX) use from four Phase 3 studies: FUTURE 2, FUTURE 3, FUTURE 4 and FUTURE 5. Methods: Overall, 397, 414, 341, and 996 pts with active PsA were randomised in FUTURE 2, FUTURE 3, FUTURE 4 and FUTURE 5, respectively. Secukinumab doses included subcutaneous (s.c.) 300 mg and 150 mg administered at baseline (BL) with loading doses at Wks 1, 2, and 3, followed by maintenance dose every 4 wks (q4w) starting at Wk 4 and s.c. secukinumab 150 mg administered at BL without loading dose, followed by q4w starting at Wk 4. Data collected up to Wk 16 were pooled. Assessments included ACR20/50/70, DAS-28 CRP, PASI 75/90, SF-36 PCS, HAQ-DI, and resolution of dactylitis, and enthesitis. Pooled analyses examined the effect of prior anti-TNF use (naïve/inadequate response or intolerance to these agents, -IR) and with/without MTX use on clinical endpoints and are reported after application of non-responder imputation for binary variables and a mixed-effects model for repeated measures for continuous variables. Results: A total of 2049 pts were included in the analysis, of which 461, 572, 335, and 681 pts received secukinumab 300 mg, 150 mg, 150 mg without load and placebo, respectively. Improvements were observed with secukinumab vs placebo for all endpoints at Wk 16 in both anti−TNF-naive and anti−TNF-IR pts and in pts with and without concomitant MTX use. Higher ACR and PASI responses and greater improvement of disease activity were observed in anti−TNF-naïve pts compared to anti−TNF-IR pts. Secukinumab 300 mg provided numerically higher ACR and PASI responses compared to the 150 mg dose particularly for anti−TNF-IR pts and in pts with no concomitant MTX use. Earlier responses were observed with secukinumab with load compared to without load primarily across ACR, DAS28-CRP and PASI endpoints. Conclusions: Secukinumab provided improvements in the signs and symptoms of active PsA regardless of previous anti-TNF therapy or concomitant MTX use. Higher response rates were generally observed in anti−TNF-naïve pts compared to anti−TNF-IR pts. Secukinumab 300 mg was associated with higher responses compared to 150 mg particularly in anti−TNF-IR pts and in pts with no concomitant MTX use. References: [1] Mease P, et al. Ann Rheum Dis. 2017;76:952–953 [2] McInnes IB, et al. Rheumatology (Oxford)2017;56:1993–2003 [3] Mease P, et al. Arthritis Rheumatol . 2017; 69 (suppl 10) Acknowledgements: The study was sponsored by Novartis Pharma AG. Disclosure of Interest: B. Kirkham Grant/research support from: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, Consultant for: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, Speakers bureau: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, P. Mease Grant/research support from: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, P. Nash Grant/research support from: Novartis, Abbvie, Roche, Pfizer, BMS, Janssen, and Celgene, Consultant for: Novartis, Abbvie, Roche, Pfizer, BMS, Janssen, and Celgene, Speakers bureau: Novartis, Abbvie, Roche, Pfizer, BMS, Janssen, and Celgene, A. Balsa Grant/research support from: Pfizer, Abbvie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB, Consultant for: Pfizer, Abbvie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB, Speakers bureau: Pfizer, Abbvie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB, B. Combe Consultant for: BMS, AbbVie, Janssen, Lilly, pfizer, Msd, Novartis, roche -chugai, ucb, s'angoisse, Speakers bureau: BMS, AbbVie, Janssen, Lilly, pfizer, Msd, Novartis, roche -chugai, ucb, s'angoisse, J. Rech Grant/research support from: BMS and Celgene, Speakers bureau: Abbvie, BMS, Celgene, Fresenius, Medicap, MSD, Novartis, Pfizer, and Roche, R. Martin Shareholder of: Novartis, Employee of: Novartis, G. Ligozio Shareholder of: Novartis, Employee of: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, L. Pricop Shareholder of: Novartis, Employee of: Novartis